‘What we have lost is patients who can’t handle the information’ – information misuse and open records access - Camilla Lyckblad (Information Research: An International Electronic Journal)
Introduction. This paper aims to broaden the understanding of information misuse by drawing on findings from an ongoing study investigating how open record access in paediatric psychiatry influences documentation practices. It explores the boundaries of what constitutes information misuse, raising the question: can individuals misuse their own information?